Application of immobilized enzyme technologies for the textile industry: a review - Soares, José C.; Moreira, Patrícia R.; Queiroga, A. Catarina; Morgado, José; Malcata, F. Xavier; Pintado, Manuela E. (Biocatalysis and biotransformation, 2011)
Abstract A number of enzymes have applications in the textile sector, as several natural fibres (e.g. cotton, wool and flax) can be subjected to processing using such natural biocatalysts. In the latest two decades, demand for industrial enzymes has increased considerably; however, the textile industry requires highly stable enzymes, and good performance at extreme values of pH and temperature. New strategies are continuously emerging for the immobilization of enzymes with superior efficiency and usage. Enzymatic immobilization can stabilize enzymes and extend their useful life. Additionally, reduction in effluent treatment costs and improvement of efficiency is possible. This paper briefly reviews the most recent research efforts pertaining to immobilization of enzymes with potential application in the textile industry.